A Study on the Informal Economy Size of Emerging Southeast Asian Nations - Quang Trung Ngo (International Journal of Advanced Science and Technology, 2020)
In many countries, the size of the informal business sector including small-scaled stores, streetvendors, private tailor shops, self-employed craftsmen, or scrap collectors, etc. even dominates theeconomy compared to the formal one. However, informal businesses are usually not easy to bemanaged and fairly assessed by the government. This could lead to an issue for the government interms of developing, exploiting, and regulating the informal sector. Recognizing the significance ofthe informal economy, this paper aims to examine the size of the informal economies of someemerging countries in the Southeast Asian region, namely Indonesia, Malaysia, Philippines, Thailand,and Vietnam. By the quantitative method using the FEM analysis, this paper finds that the existence ofinformal economies in these countries is not small and there are large disparities between countries.In which, Thailand exists the largest informal economy size, while Vietnam is the smallest one.Additionally, the study identifies that the tax burden is the main factor leading to the informaleconomy among other variables, namely money supply, tax, saving interest rate, personalconsumption, and GDP per capita. In general, the study aid policy-makers in Southeast Asiancountries to have a better understanding of the factors leading to the informal economy, thereby theycan effectively manage the economy. In many countries, the size of the informal business sector including small-scaled stores, streetvendors, private tailor shops, self-employed craftsmen, or scrap collectors, etc. even dominates theeconomy compared to the formal one. However, informal businesses are usually not easy to bemanaged and fairly assessed by the government. This could lead to an issue for the government interms of developing, exploiting, and regulating the informal sector. Recognizing the significance ofthe informal economy, this paper aims to examine the size of the informal economies of someemerging countries in the Southeast Asian region, namely Indonesia, Malaysia, Philippines, Thailand,and Vietnam. By the quantitative method using the FEM analysis, this paper finds that the existence ofinformal economies in these countries is not small and there are large disparities between countries.In which, Thailand exists the largest informal economy size, while Vietnam is the smallest one.Additionally, the study identifies that the tax burden is the main factor leading to the informaleconomy among other variables, namely money supply, tax, saving interest rate, personalconsumption, and GDP per capita. In general, the study aid policy-makers in Southeast Asiancountries to have a better understanding of the factors leading to the informal economy, thereby theycan effectively manage the economy.